Case report: Imaging findings of true thymic hyperplasia at 18F-FDG PET/CT in an infant - Ren, Jiazhong; Fu, Zheng; Zhao, Yaqing (Frontiers in Oncology, 2023)
True thymic hyperplasia (TTH) in children is rare and difficult to distinguish from other thymic tumors such as thymoma and thymic carcinoma. A 3‐year‐old girl underwent an 18F‐fluorodeoxyglucose (18F‐FDG) positron emission tomography (PET)/computed tomography (CT) scan (18F‐FDG PET/CT) and a chest CT scan to evaluate an anterior mediastinal mass. 18F‐FDG PET/CT revealed a mediastinal mass showing heterogeneously increased FDG uptake with a maximum standardized uptake value (SUVmax) of 7.1. Eventually, postoperative pathological diagnosis demonstrated TTH. So far, there are no reports of 18F‐FDG PET/CT imaging of this disease.